Instilling the Character of Religious Tolerance Through School Culture in Kindergarten - Gheiska Enggar Bonita; Edi Waluyo (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Instilling the character of religious tolerance is a strategy in forming children's attitudes that respect diversity and differences. In kindergartens, the character of religious tolerance is very important to instill, but the lack of educators, lack of parental awareness, and students who do not yet have a character of tolerance are problems that often arise in the school environment. School culture can include traditions, habits, and interactions that occur in the school environment. This study aims to analyze the instillation of the character of religious tolerance through school culture in kindergartens. The subjects needed in this study were the principal, four educators, and kindergarten students. This study uses a qualitative ethnographic research method. In this study, data were collected through observation, interviews and documentation. Data analysis used data reduction, data presentation and drawing conclusions. Then to validate the truth of the data using source triangulation techniques. The results of the study showed that the instillation of the character of religious tolerance through school culture was carried out by habituation such as reading Iqro every morning, praying before and after learning, and extracurricular activities such as BTA and reading the Bible. In conclusion, the instillation of the character of religious tolerance through school culture is very important with habituation and evaluating supporting and inhibiting factors.